2023
DOI: 10.21203/rs.3.rs-2831214/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Innovative i-PRF semisurgical method for gingival augmentation and root coverage in thin periodontal phenotypes: A preliminary study

Abstract: Objectives The aim of this study was to evaluate the effect of injectable platelet-rich fibrin (i-PRF) on gingival thickness (GT) and gingival recession (GR) in individuals with thin periodontal phenotypes using a semisurgical approach.Materials and methods In this prospective study, i-PRF was applied via a semisurgical method to augment 53 tooth regions with thin periodontal phenotypes. i-PRF injection was applied to the relevant areas in 4 sessions at an interval of 10 days. GT, GR, keratinized tissue width … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
(43 reference statements)
0
1
0
1
Order By: Relevance
“…24 Diantaranya, konsentrat trombosit mendapatkan popularitas di kalangan dokter karena keefektifannya dalam mendukung penyembuhan luka. 25…”
Section: Pendahuluanunclassified
“…24 Diantaranya, konsentrat trombosit mendapatkan popularitas di kalangan dokter karena keefektifannya dalam mendukung penyembuhan luka. 25…”
Section: Pendahuluanunclassified
“…The latest scientific progress in PRF is injectable PRF (I-PRF) [ 44 , 45 ]. Previously conducted research reported that possessing shortcomings of PRF over platelet-rich plasma (PRP) is that it is obtained only in a gel form, which limits its applications [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%